LIMBAH PERTANIAN UNTUK PERBAIKAN KUALITAS LAHAN DAN PENINGKATAN PRODUKSI PADI SAWAH DI KECAMATAN PINANG BELAPIS KABUPATEN LEBONG - Priyono Prawito; Gita Mulyasari; Madani Hatta (DHARMA RAFLESIA, 2018)
The people of Pinang Belapis face with the problem of declining soil quality and difficult to purchase anorganic fertilizer because of high prices and uncertain availability. The purposes of this community service are (1) to train the composting of agricultural waste materials to substitute inorganic fertilizer needs with compost and improve the quality of agricultural land by utilizing the results of composting; (2) to apply the compost to sample plots of land; (3) giving extension about the importance of organic/compost for soil and plants. Composting training is given to the boards of farmer groups. Besides composting, counseling about importance of organic fertilizer and compost in improving and maintaining soil fertility and its benefit to plants is also performed. Compost material consisting of a mixture of agricultural wastes and shrubs around the site composting is collected, chopped, and stacked layer by layer, each layer height of 20 cm. Microbes Add-Compost "Promi" is dissolved in water, and sprinkle on each layer and stacks of compacted organic material. Coating and watering is done until the compost runs out in order. Heaps of organic matter plastikagar closed with the humidity up. Compost is observed every week to measure the increase in temperature and decrease in the volume of compost. After 3 weeks, the compost is ready for harvest, as indicated by the shrinking volume of compost to about 50%, the color changes to dark brown, crumbly brittle materials, the smell is not overpowering. Then the compost is applied to the example land plot for demonstration. Keywords: organic material, compost, soil quality, agricultural waste, agricultural land